2021
DOI: 10.2478/ebtj-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of scarification method on seed germination of the terrestrial orchid Anacamptis laxiflora (Lam.)

Abstract: A critical step during in vitro sexual propagation of terrestrial orchids is the treatment of the microscopic seeds with a disinfecting solution that kills bacteria and fungi attached to the seeds. This treatment is necessary to prevent infection of the culture vessels. At the same time, the treatment serves to scarify the seeds, a process that disrupts seed dormancy and initiates germination. The literature is inconclusive with respect to the proper combination of disinfecting solution strength and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This sensitivity to sodium hypochlorite may be attributable to various factors; unfortunately, there is little information available to elucidate these in Spiranthes . Thin seed coats, the presence of air space in the integument and between the integument and the embryo, the structural and chemical composition of the integument and seed coat, the presence of different cuticular substances, and “wettability” have all been cited as factors influencing the response of orchid seed coats to chemical reagents (Molvray and Kores, 1995 ; Arditti and Ghani, 2000 ; Deconninck and Gerakis, 2021 ). One issue with such a shortened scarification period using sodium hypochlorite is that bacterial and fungal spores may not be completely killed during the process, leading to contamination of cultures before germination and initial seedling development is complete.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sensitivity to sodium hypochlorite may be attributable to various factors; unfortunately, there is little information available to elucidate these in Spiranthes . Thin seed coats, the presence of air space in the integument and between the integument and the embryo, the structural and chemical composition of the integument and seed coat, the presence of different cuticular substances, and “wettability” have all been cited as factors influencing the response of orchid seed coats to chemical reagents (Molvray and Kores, 1995 ; Arditti and Ghani, 2000 ; Deconninck and Gerakis, 2021 ). One issue with such a shortened scarification period using sodium hypochlorite is that bacterial and fungal spores may not be completely killed during the process, leading to contamination of cultures before germination and initial seedling development is complete.…”
Section: Discussionmentioning
confidence: 99%
“…One issue with such a shortened scarification period using sodium hypochlorite is that bacterial and fungal spores may not be completely killed during the process, leading to contamination of cultures before germination and initial seedling development is complete. Recent research has shown that soaking seeds in a sucrose solution before chemical scarification can cause bacterial and fungal spores to germinate, making them more sensitive to the chemical regent and thereby increasing the efficacy of the sterilant, but this has not been tested with North American Spiranthes (Deconninck and Gerakis, 2021 ). Other scarification reagents should be tested, and alternative options such as ultrasonic treatment after an initial chemical sterilization or culture of immature embryos should be attempted to diversify the range of techniques for successfully germinating Spiranthes seeds (Miyoshi and Mii, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation